Motivational Teaching Strategies within Saudi University EFL Classrooms: How to Improve Students’ Achievement? - Elashhab , Seham (International Journal of Language and Literary Studies, 2020)
Motivation is essential because it highly contributes to achievement. Teachers need to motivate their students in order to develop a positive outcome. Research on motivation for foreign language learning has shown that teachers should be aware of their actions and behaviors in classroom because it is very likely that they can demotivate learners. This study explores how motivational strategies used by English as a foreign language (EFL) teachers could increase the motivation of students to learn English as a foreign language. Participants included five EFL teachers along with one hundred first-year female students. The students completed a survey while the teachers took part in an interview. Both measures aimed to explore the attitudes of both teachers and students towards motivation in the foreign language classroom. Results showed that the most used motivational strategies were: resources that satisfy the students’ needs and interests, group work, active participation in class, and praises and rewards. The findings of this study can contribute to teachers’ knowledge of the motivational strategies that work best for students especially those that are pertinent to the Saudi context to improve their current teaching methods and can contribute also to further research on motivation.